IL-1α/IL-1R1 expression in chronic obstructive pulmonary disease and mechanistic relevance to smoke-induced neutrophilia in mice. - Fernando M Botelho; Carla M T Bauer; Donna Finch; Jake K Nikota; Caleb C J Zavitz; Ashling Kelly; Kristen N Lambert; Sian Piper; Martyn L Foster; James J P Goldring; Jadwiga A Wedzicha; Jennifer Bassett; et al. (PLoS ONE)
Background Cigarette smoking is the main risk factor for the development of chronic obstructive pulmonary disease (COPD), a major cause of morbidity and mortality worldwide. Despite this, the cellular and molecular mechanisms that contribute to COPD pathogenesis are still poorly understood. Methodology and principal findings The objective of this study was to assess IL-1 α and β expression in COPD patients and to investigate their respective roles in perpetuating cigarette smoke-induced inflammation. Functional studies were pursued in smoke-exposed mice using gene-deficient animals, as well as blocking antibodies for IL-1α and β. Here, we demonstrate an underappreciated role for IL-1α expression in COPD. While a strong correlation existed between IL-1α and β levels in patients during stable disease and periods of exacerbation, neutrophilic inflammation was shown to be IL-1α-dependent, and IL-1β- and caspase-1-independent in a murine model of cigarette smoke exposure. As IL-1α was predominantly expressed by hematopoietic cells in COPD patients and in mice exposed to cigarette smoke, studies pursued in bone marrow chimeric mice demonstrated that the crosstalk between IL-1α+ hematopoietic cells and the IL-1R1+ epithelial cells regulates smoke-induced inflammation. IL-1α/IL-1R1-dependent activation of the airway epithelium also led to exacerbated inflammatory responses in H1N1 influenza virus infected smoke-exposed mice, a previously reported model of COPD exacerbation. Conclusions and significance This study provides compelling evidence that IL-1α is central to the initiation of smoke-induced neutrophilic inflammation and suggests that IL-1α/IL-1R1 targeted therapies may be relevant for limiting inflammation and exacerbations in COPD.